Orodental biopsies in females: a 23 year study - Sharma, Bishnu Prasad; Baral, Reetu (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: Tissue diagnosis is an essential step to come to a confirmed diagnosis in oral lesions where clinical examination alone can often be difficult and inaccurate. The aim of this study was to assess the use of histopathological services by the dental department and to correlate the clinicopathological diagnosis in females who visited Patan Hospital. Methods: This is a histopathological database analysis of dental biopsies in 23 years from 1989 to 2012 in Patan Hospital. The variables studied were age, sex, clinical and histopathological diagnosis. SPSS version 16 was used as an analytical tool. Results: Out of 396 dental biopsies 203 (51.3%) were females and 193 (48.7%) were males with mean age 34.34 years and standard deviation of 17.9 years. Malignant tumor was seen in six female cases, all of which was squamous cell carcinoma. The total number of neoplastic and non-neoplastic conditions was 44% and 56% respectively in both the sexes. Conclusion: Most diagnoses were benign in nature and had an inflammatory etiology.